Teachers' Perceptions of the Deep Learning Approach and Its Implementation in School Learning - Dwi Sudarti; Addy Septyawan (CV. Media Digital Publikasi Indonesia, 2026)
This study aims to analyze teachers' perceptions of the deep learning approach and its implementation in learning at the elementary and secondary school levels in Melawi Regency. The research was carried out in January-March 2025 and used a mixed methods method with a sequential explanatory design that combines quantitative and qualitative analysis. Quantitative data was collected through questionnaires to 20 teachers at SD Negeri 13 Nanga Pinoh and SMP Negeri 2 Pinoh Utara, while qualitative data was obtained through in-depth interviews with four teachers who were selected purposively. The results showed that teachers' perception of deep learning was in the very positive category with an average percentage of 84.64% in the dimensions of concept understanding, attitude, implementation, as well as supporting factors and obstacles. Teachers understand that deep learning emphasizes meaningful experiences, reflection, collaboration, and the relevance of the material to students' real lives. The implementation of deep learning is considered quite good even though it still faces several obstacles such as time constraints, authentic assessments, and the use of learning technology. Qualitative findings reinforce quantitative outcomes through real-world descriptions of exploratory and project-based learning practices in the classroom. This study concludes that teachers have a high readiness to implement deep learning as part of the learning transformation in the Independent Curriculum, and emphasizes the need for continuous training and school support.